COMPARISON OF CLINICAL AND BIOCHEMICAL VARIABLES BETWEEN PATIENTS ON TWICE A WEEK DIALYSIS REGIME HAVING DIFFERENT RESIDUAL RENAL FUNCTION – A JACK IN THE BOX - AFZAL, A; RAFIQUE, Z; GULZAR, A; RAUF, MA; TALAL, A (Biological and Clinical Sciences Research Journal, 2022)
In resource limiting counties, it is a general observation that patients with chronic kidney disease have undergone twice a week dialysis even though they need thrice a week dialysis regime. This not only increases the burden on hospital emergencies but also affects the quality of life of the patients. The current analysis aims to assess the quality of life, biochemical variables, and adverse events in patients on twice a week dialysis having renal urea clearance less than 2 mL/min/1.73 m2 (Kr < 2 mL/min/1.73 m2) as compared to those undergoing twice weekly dialysis having renal urea clearance Kr greater than 2 mL/min/1.73 m2. This investigation was carried out at the Department of Nephrology, in Services Hospital Lahore. The study involved a total of sixty participants. They were then split into two separate groups. Thirty participants in Group A were on twice a week dialysis and had Kr > 2 mL/min/1.73 m2, whereas in Group B, participants with the same age and sex were also on twice a week dialysis regime but had Kr < 2 mL/min/1.73 m2. According to the 2006 Kidney Disease Outcome Quality Initiative (KDOQI) Clinical Practice Guidelines, individuals with renal urea clearance (Kr) less than 2 mL/min/1.73 m2 should undergo thrice-weekly hemodialysis. Therefore, Group B was not following the recommended weekly dialysis schedule. The primary objective of the study was to assess the difference in biochemical variables and the last sixmonth emergency visits and the second goal was to determine the quality of life by using the Sf-12 QoL questionnaire. The trial involved a total of sixty participants receiving twice-weekly dialysis. Males made up 59% of the study's participants. The participants' average age was 42.18 ± 18.10 years. Group A had a mean age of 38.9 ± 17.6 years, while group B had a mean age of 41.2 ± 14.9 years. Systolic blood pressure was significantly higher in group B compared to group A (p=0.04). The biochemical examination revealed that group B had significantly lower levels of albumin (p=0.001) and higher levels of urea and calcium (p=0.01 and 0.046, respectively) than group A. It was discovered that group B had significantly more hospital visits than group A (p=0.003). Using the SF-12 to measure quality of life, there was no discernible difference between the groups. The patients were on twice a week dialysis despite their renal urea clearance of less than 2 mL/min/1.73 m2 having compromised clinical and biochemical parameters. In addition, they also had greater number of emergency visits. Thus, we can conclude that thrice a weekly dialysis is a recommended regime for effected patients having Kr less than2 mL/min/1.73 m2.